Decisão de engravidar no contexto da ZIKA: uma abordagem qualitativa - Santos, Mayara Paz Albino dos (2021)
The Zika epidemic in the 2015-2016 period was a public emergency with personal, social, economic and political repercussions that strongly affected maternal and child health in Brazil. This led to recommendations by health authorities to postpone pregnancy and a general decrease in the birth rate in the country. Currently, the disease is no longer an emergency, but its effects continue to be felt and Zika remains an important public health issue. The aim of the present study is to understand the decision to get pregnant by women in the context of a Zika virus (ZIKV) epidemic in the light of the recommendations of health authorities. The research was developed in a qualitative approach. 51 face-to-face interviews were carried out with women of childbearing age in the city of Fortaleza, Ceará, Brazil, using an open semi-structured research guide based on the methodology Rapid Ethnographic Assessment (REA). The guide contained topics based on initial pilot interviews and a review of the scientific literature. The sampling was intentional and attempted to include a diversity of women from different social classes, ages and reproductive stages. The average profile of the sample was women aged 20 to 29 years, with complete high school, mixed race, married, with children and with some type of paid activity. The results demonstrate the multidimensional character of decision-making to become pregnant and, in contradiction to the broader national demographic evidence, the Zika epidemic did not affect the intention to become pregnant, knowledge, the use of contraceptives or other methods of family planning. It was also identified, inconsistent use of family planning methods and ambivalence in relation to the use of contraceptives, suggesting a complex socio-cultural panorama where these women are inserted. Despite recommendations from health authorities to provide health professionals with advice on the risks of pregnancy during the Zika epidemic, this action was never implemented by the state. The declarative one-dimensional recommendation to avoid pregnancy appears to be insufficient to address this complex decision. The inadequacy of the health system's response to prevention highlights the need for careful development of integrated and comprehensive interventions, in addition to thorough planning in the implementation of health policies and actions not only for Zika, but also for other possible epidemics.